2019
DOI: 10.17344/acsi.2019.5139
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Ibuprofen and Silicified-MCC: Characterization, Drug Release and Modeling Approaches

Abstract: Analysis of the binding interactions of ibuprofen and silicified-microcrystalline cellulose (SMCC) has been undertaken. Co-processing of ibuprofen with SMCC was carried out by solid state ball milling, and aqueous state equilibration followed by freeze drying to investigate the effect of silicified-microcrystalline cellulose on ligand. Molecular docking study revealed that ibuprofen formed complex through hydrogen bond with microcrystalline cellulose (MCC) and silicon dioxide (SiO 2); the binding energy betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The calculated n value appeared less than 0.5 of all the formulations. The n value of Peppas model suggested that the release mechanism was predominantly diffusion controlled [54][55][56] . Films containing kaolin showed higher t 50 value than films without kaolin.…”
Section: Resultsmentioning
confidence: 99%
“…The calculated n value appeared less than 0.5 of all the formulations. The n value of Peppas model suggested that the release mechanism was predominantly diffusion controlled [54][55][56] . Films containing kaolin showed higher t 50 value than films without kaolin.…”
Section: Resultsmentioning
confidence: 99%
“…For visualizing the surface morphology of the experimental crystal products scanning electron microscopy (Carl ZEISS Sigma 300, India) was used. 17 During the study, the crystalline morphology of the samples was visualized by introducing high beam of electrons and through 0.5-1.5 kV accelerated voltage.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…Similar reports for the use of water as release medium for poorly soluble drugs have already been reported earlier including ibuprofen. 17,[23][24][25][26][27][28][29][30][31][32][33] Hu et al reported in vitro drug release of IBU from the experimental micro emulsion in distilled water. 26 It was found that in vitro release profiles of IBU did not show much change in different drug release medium, i.e.…”
Section: Dissolution Of Drugmentioning
confidence: 99%
“…The small changes in the peak shifting and intensity are the indication of amorphization of the drug in the film formulations. [15][16][17][18]…”
Section: Ftir Studymentioning
confidence: 99%